2021
DOI: 10.1177/08862605211027998
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Polyvictimization in a Family Justice Center: Lessons Learned From a Demonstration Project

Abstract: There is a growing interest in developing comprehensive assessments that measure intimate partner violence (IPV) alongside other adverse events that correlate with IPV and compound its effects. One promising line of research in this area has focused on the impact of exposure to multiple types of victimization, i.e., polyvictimization. The purpose of this study is to examine the experience of administration of a polyvictimization tool from staff and client perspectives in order to inform future tool development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…This finding indicates that IPV perpetrations that involve physical violence tend to occur with other forms of IPV. Survivors often disclose a single violent incident or just one episode of their entire IPV experience when seeking help rather than revealing all the IPV they have experienced in their lives, possibly because they feel ashamed or because help sources are reluctant to ask sensitive questions (Dagenhardt et al, 2021; Evans & Feder, 2016). However, our results showed that many survivors experience multiple forms of violence from a single perpetrator.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that IPV perpetrations that involve physical violence tend to occur with other forms of IPV. Survivors often disclose a single violent incident or just one episode of their entire IPV experience when seeking help rather than revealing all the IPV they have experienced in their lives, possibly because they feel ashamed or because help sources are reluctant to ask sensitive questions (Dagenhardt et al, 2021; Evans & Feder, 2016). However, our results showed that many survivors experience multiple forms of violence from a single perpetrator.…”
Section: Discussionmentioning
confidence: 99%